Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 7.5

Ex 7.5, 1

Ex 7.5, 2

Ex 7.5, 3 Important

Ex 7.5, 4

Ex 7.5, 5

Ex 7.5, 6 Important

Ex 7.5, 7 Important

Ex 7.5, 8

Ex 7.5, 9 Important

Ex 7.5, 10

Ex 7.5, 11 Important

Ex 7.5, 12

Ex 7.5, 13 Important

Ex 7.5, 14 Important

Ex 7.5, 15

Ex 7.5, 16 Important

Ex 7.5, 17

Ex 7.5, 18 Important You are here

Ex 7.5, 19

Ex 7.5, 20 Important

Ex 7.5, 21 Important

Ex 7.5, 22 (MCQ)

Ex 7.5, 23 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 7.5, 18 Integrate the function (𝑥2+ 1)(𝑥2+ 2)/(𝑥2+ 3)(𝑥2+ 4) (𝑥^2 + 1)(𝑥^2 + 2)/(𝑥^2 + 3)(𝑥^2 + 4) " " Let t = 𝑥^2 = (𝑡 + 1)(𝑡 + 2)/(𝑡 + 3)(𝑡 + 4) = (𝑡^2 + 3𝑡 + 2)/(𝑡^2 + 7𝑡 + 12) = 1 + (−4𝑡 −10)/(𝑡^2 + 7𝑡 + 12) = 1 + (−(4𝑡 + 10))/(𝑡 + 3)(𝑡 + 4) Rough = 1 − ( (4𝑡 + 10))/(𝑡 + 3)(𝑡 + 4) We can write (4𝑡 + 10)/((𝑡 + 3) (𝑡 + 4) ) = 𝐴/((𝑡 + 3) ) + 𝐵/((𝑡 + 4) ) (4𝑡 + 10)/((𝑡 + 3) (𝑡 + 4) ) = (𝐴(𝑡 + 4) + 𝐵(𝑡 + 3))/((𝑡 + 3) (𝑡 + 4) ) Cancelling denominator 4𝑡−10 = 𝐴(𝑡+4)+𝐵(𝑡+3) Putting t = − 4 in (1) 4(−4)+10 = 𝐴(−4+4)+𝐵(−4+3) −16+10 = 𝐴×0+𝐵(−1) …(1) −6 = 𝐴×0+𝐵(−1) −6 = −𝐵 𝐵 = 6 Putting t = −3 in (1) 4𝑡−10 = 𝐴(𝑡+4)+𝐵(𝑡+3) 4(−3)+10 = 𝐴(−3+4)+𝐵(−3+3) −12+10 = 𝐴×1+𝐵×0 −2 = 𝐴 𝐴 = −2 Hence we can write (4𝑡 + 10)/((𝑡 + 3) (𝑡 + 4) ) = (−2)/((𝑡 + 3) ) + 6/((𝑡 + 4) ) Putting back t = 𝑥^2 (4𝑥^2 − 10)/((𝑥^2 + 3) (𝑥^2 + 4) ) = (−2)/((𝑥^2 + 3) ) + 6/((𝑥^2 + 4) ) Therefore ∫1▒(𝑥2+ 1)(𝑥2+ 2)/(𝑥2+ 3)(𝑥2+ 4) = ∫1▒〖1−[(−2)/((𝑥^2 + 3) ) + 6/((𝑥^2 + 4) )] 〗 𝑑𝑥 = ∫1▒1. 𝑑𝑥 + ∫1▒2/((𝑥^2 + 3) ) 𝑑𝑥 − ∫1▒6/((𝑥^2 + 4) ) 𝑑𝑥 = ∫1▒1. 𝑑𝑥 + 2∫1▒1/(𝑥^2 + (√3)^2 ) 𝑑𝑥 − 6∫1▒1/((𝑥^2 +2^2 ) ) 𝑑𝑥 = 𝑥 + 2 × 1/√3 tan^(−1)〖 𝑥/√3〗 − 6 × 1/2 tan^(−1)〖 𝑥/2〗+𝐶 = 𝒙 + 𝟐/√𝟑 〖𝒕𝒂𝒏〗^(−𝟏)(𝒙/√𝟑)−𝟑 〖𝒕𝒂𝒏〗^(−𝟏)(𝒙/𝟐)+𝑪